The next generation of farmers: successes and new opportunities: Reader for Brussels Briefing 53 - Boto, Isolina; Mofolo, Lebo (Technical Centre for Agricultural and Rural Cooperation, 2018)
The global population is on track to surpass 9 billion by 2050 and exceed 11 billion by the end of the century. The world’s 500 million smallholder farms produce around 80% of our food and it is they who will have to carry the burden of increasing food production by over 70%. The information in this document was compiled as background reading material for the 53rd Brussels Briefing on The next generation of farmers: successes and opportunities.